PENGARUH PROMOSI DAN ORIENTASI PASAR TERHADAP KEPUASAN PELANGGAN DENGAN MEDIASI KUALITAS PELAYANAN PADA DEALER MOTOR HONDA PONTANG PERKASA KABUPATEN SERANG - Siti Hartati; Listiawati Listiawati; Kenedi Kenedi (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
Customer satisfaction is the key for companies to win business competition to achieve this the role of promotion, market orientation and service quality becomes very important. The purpose of this study is to analyze the influence of promotion and market orientation on customer satisfaction by mediating service quality at Honda Pontang Perkasa motorcycle dealers, Serang Regency. This study used primary data from the results of the distribution of questionnaires to 160 respondents using accidental sampling or convenience sampling techniques. Method of analysis using the PLS-SEM approach. The results of the study show that promotion has a direct effect on service quality and customer satisfaction, market orientation does not affect service quality and customer satisfaction and service quality has a direct effect on customer satisfaction, in addition, there is a mediation effect between promotion on customer satisfaction through service quality and no mediation effect between market orientation and customer satisfaction through service quality